Кирень куректон: очеркъёс, повестьёс / Георгий Грязев ; [редакторез С. В. Матвеев] - Грязев Георгий Геннадьевич (Удмуртия, 1996)
Экземпляры: (20231009) / Инвентарный номер: 25379 / Цена: 6.00 / Сис.шифр: 84(2=664.1) / Авт.знак: Г 92 / ГРНТИ: 17.82.32 / ББК: 84(2=664.1)